A new species of Uleiorchis (Orchidaceae, Gastrodieae) from the Atlantic Forest of Brazil - Smidt, Eric C; Engels, Mathias E.; Bolson, Mônica; Berg, Cássio Van Den (Phytotaxa, 2015)
A new species from the Brazilian Atlantic Forest, Uleiorchis prataënsis, is described, with illustrations and scanning electron micrographs of pollinaria and seeds. Comments on the new species are presented with a key to the species of the genus. Because the phylogenetic position of Uleiorchis has not been previously evaluated with DNA data, we estimated phylogenetic relationships using nrITS sequence data to confirm that this genus is a member of Gastrodieae. The results indicate with high support in both maximum parsimony and maximum-likelihood analyses that both species of Uleiorchis are sister and members of this tribe. Finding a new species in a relatively well-collected place such as Paraná State supports the status of high diversity hotspot for the Atlantic Forest and demonstrates the need for more fieldwork on orchids and other families.